Evaluating basic motor competence in Italian children post-COVID-19 pandemic - Monacis, Domenico (Annales kinesiologiae (Koper), 2024)
Motor competence assessment represents one of the most important topics in the field of motor development and physical education. The present cross-sectional study aims to assess basic motor competence, self-perception and enjoyment during physical activity (PA) in a sample of normal weight, and overweight or obese children post-COVID-19 pandemic. The participants (N = 107, age = 8-9 years old) were recruited from an experimental project conducted in Lecce (Italy). The motor competence assessment was undertaken using MOBAK 3-4 protocol, and self-perception and enjoyment were evaluated with two validated questionnaires. A multivariate analysis of variance (MANOVA) was performed to assess the effect of gender and BMI on the variables considered. Despite the MANOVA results indicating no significant interaction effects between variables, a significant main effect was found for gender F(10,93) = 2.353, p = .013, ?2 = 0,218 and BMI cutoff F(10,93) = 2.351, p = .013, ?2 = 0,218. Moreover, an independent t-test highlighted significant differences in catching, dribbling, balanc-ing and object movement according to gender (p < .05), and in balancing, rolling and self-movement according to BMI cutoff (p < .05). Self-efficacy differed significantly between males and females, while no significant effect was found for enjoyment. Further studies should investigate the effect of BMI and factors related to physical activity on motor competence development.
Keywords: debelost; motorična sposobnost; motorični razvoj; otroci; samoučinkovitost; spol; telesna aktivnost